Estimasi Biomassa, Cadangan Karbon, Produksi O2 dan Nilai Jasa Lingkungan Serapan CO2 Tegakan Hutan di Taman Hutan Raya Abdul Latief Sinjai Timur - Irma Sribianti; Sultan; Muthaminnah; M Daud; Nirwana; Andi Aziz Abdullah; Ashar Sardiawan (Jurnal Hutan dan Masyarakat, 2022)
ABSTRACT: This study aims to determine the potential of biomass, carbon stocks, and carbon dioxide (CO2) absorption in forest stands in the Abdul Latief Forest Park, Sinjai District, South Sulawesi Province. Measurement of biomass at various levels of growth was carried out by making plots of 20 with a size of 20 m x 20 m for tree level, 10 m x 10 m for pole level and 5 m x 5 m for sapling level. Tree biomass, poles and saplings are calculated using allometric equations for tropical wood species in Indonesia. Measuring carbon stocks is done by multiplying biomass with a conversion rate of 0.47 (47%) while carbon dioxide (CO2) absorption is calculated by multiplying the average annual growth of biomass with a conversion rate of 1.4667 obtained from the photosynthesis equation. Based on the results of the study showed that the biomass content of forest stands in the Abdul Latief Forest Park was 192.10 Ton/Ha, carbon stocks in the forest stand in the Abdul Latief Forest Park were 90.28 Ton/Ha, the oxygen production was 385,59 Ton/Ha and the absorption of carbon dioxide (CO2) in forest stands in Abdul Latief Forest Park of 13.13 Tons/Ha/Year oksigen. Value of Environmental services carbon dioxide was Rp. 35.267.664/Ton/Tahun Keywords : Biomass, Carbon dioxide absoption, Oxygen Production, Value of Enviromental Services, Forest Park